RESPONSE SURFACE METHODOLOGY-AIDED DEVELOPMENT OF PIRFENIDONE-LOADED SOLID LIPID NANOPARTICLES FOR INTRAPULMONARY DRUG DELIVERY SYSTEM - KWOK, KEVIN; SUHARIYONO, GATOT; SURINI, SILVIA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aims to determine the optimized Pirfenidone-loaded Solid Lipid Nanoparticles (P-SLN) formula for Intrapulmonary Drug Delivery System (IPDDS) using Response Surface Methodology (RSM). Methods: Box-Behnken design was applied to create fifteen P-SLN formulas comprising three independent variables, namely lipid-to-drug ratio, polymer type, and polymer concentration, and three dependent variables, including particle size, Polydispersity Index (PDI), and entrapment efficiency. The P-SLNs were prepared by solvent injection followed by the ultrasonication method. Those formulas were optimized with the RSM approach using the Design Expert®. Then, the optimized P-SLN was further characterized for morphology, moisture content, aerodynamic performance, and dissolution profile. Results: The optimization process, assisted by RSM, determined that the optimized P-SLN had a lipid-to-drug ratio of 6:1 and contained 0.5% Plasdone K-29/32. The resulting P-SLN had a spherical shape with a particle size of 212.7 nm, a PDI of 0.39, an entrapment efficiency of 95.02%, and a low moisture content of 1.59%. The optimized P-SLN also exhibited appropriate IPDDS required characteristics, including a Mass Median Aerodynamic Diameter (MMAD) ranging from 0.540–12.122 μm and a Respirable Fraction (RF) of 12.4%. Moreover, the release of pirfenidone from this optimized formula was 89.61% and 69.28% in pH 4.5 and 7.4 buffer media, respectively, in 45 min through a combination of diffusion and polymer swelling mechanisms. Conclusion: The optimized P-SLN showed promising potential as an IPDDS for pirfenidone.